INDONESIA GOVERNMENT GRANTED 7 COMPULSORY LICENCES TO PROMOTE ACCES TO HIV RELATED MEDICINES - Velásquez, Germán (Vitae, 2013)
“Starting with Malaysia in 2003, many Asian countries are now taking action to promote cheaper medicines through compulsory licensing, with Indonesia being the most recent case. Recent government actions by Indonesia and India to issue compulsory licenses –CL– are extending the trend in Asia to increase access to cheaper medicines for treating serious ailments, especially those related to HIV/AIDS, cancer and Hepatitis B”. In recent years, a number of countries have issued licenses to improve access to medicines, including, Thailand, Brazil, Malaysia, Zambia, Ecuador and India, among others. Indonesian President Susilo Bambang Yudhoyono issued a decree on 3rd September 2012 that allows the government to use patents for seven HIV/AIDS and hepatitis B medicines. “We will ensure the availability of good quality, safe and effective generic versions of anti-retroviral and anti-viral drugs,” said HM Subuh, Infectious Disease Control Director at the Indonesian Health Ministry, as quoted in The Jakarta Post on 19th October.